Laboratory scale study on assessment of various geotextile materials for reduction of sediments from a soil surface - Zeshan, M.T. (Institute of Electrical and Electronics Engineers Inc., 2021)
Barren steep slopes in a watershed and along a roadside, such as embankments, cause degradation of top layer of soil surface. This triggers to expose sub-surface layers of soil, making them fragile for further potential deterioration and ultimately increasing sediment detachment from the surfaces causing silting, and sedimentation in rivers and waterbodies. This process is considered as the major cause of soil erosion which badly affects the quality of water and sustainability of the surrounding waterbodies. This study conducted a laboratory-scale investigation to assess performance of various land covers for reduction of turbidity and suspended solids from a soil surface in response to various rainfall intensities and slope angles. The investigation was performed on five different soil surface covers such as vegetation, coir, polyester, and palm geotextiles (partially fully covered). The study was conducted under two variable conditions: (i) slope variation: mild and steep slopes viz., 30° and 45° and (ii) rainfall variation: average and severe rainfall intensities viz., 40 and 60 mm/hr. The study examined suspended solids and turbidity in surface runoff based on the aforementioned climatic conditions. The results showed a significant difference in performance of the geotextile materials for controlling suspended solids and turbidity. Overall, the results indicated that palm geotextile was most effective in reducing turbidity (95) and suspended solids (84) as compared to other surface covers under same climatic conditions. © 2021 IEEE.